The Influence of Work-Life Balance on Job Satisfaction Through the Mediation of Employee Work Stress at CV Satya Dharma Transport - Luh Danisha Aulia; Made Surya Putra (International Journal of Management Research and Economics, 2025)
Job satisfaction is a critical element for the sustainability of a company. The relationship between personal and professional life balance, commonly referred to as work-life balance, and job satisfaction has garnered significant attention because work-life balance can influence employees' satisfaction levels with their jobs. On the other hand, work stress often hinders the achievement of optimal job satisfaction. This study aims to analyze the effect of work-life balance on job satisfaction with work stress as a mediating variable. The research employs a quantitative approach conducted on the employees of CV Satya Dharma Transport, located at Jl. Bumbak Dauh No. 84, Umalas, Bali, with a total sample of 32 employees obtained through a saturated sampling method. Data collection was carried out through interviews and questionnaires. The analytical technique used is Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. The results of the study indicate that work-life balance has a positive and significant effect on job satisfaction, work-life balance has a negative and significant effect on work stress, work stress has a negative and significant effect on job satisfaction, and work stress significantly mediates the effect of work-life balance on job satisfaction.